Efficacy and safety of suvratoxumab for prevention of Staphylococcus aureus ventilator-associated pneumonia (SAATELLITE): a multicentre, randomised, double-blind, placebo-controlled, parallel-group, phase 2 pilot trial. Issue 9 (September 2021) - François, Bruno; Jafri, Hasan S; Chastre, Jean; Sánchez-García, Miguel; Eggimann, Philippe; Dequin, Pierre-François; Huberlant, Vincent; Viña Soria, Lucia; Boulain, Thierry; Bretonnière, Cédric; Pugin, Jérôme; Trenado, Josep; et al.
Summary: Background: Staphylococcus aureus remains a common cause of ventilator-associated pneumonia, with little change in incidence over the past 15 years. We aimed to evaluate the efficacy of suvratoxumab, a monoclonal antibody targeting the α toxin, in reducing the incidence of S aureus pneumonia in patients in the intensive care unit (ICU) who are on mechanical ventilation. Methods: We did a multicentre, randomised, double-blind, placebo-controlled, parallel-group, phase 2 pilot trial at 31 hospitals in Belgium, the Czech Republic, France, Germany, Greece, Hungary, Portugal, Spain, and Switzerland. Eligible patients were in the ICU, aged ≥18 years, were intubated and on mechanical ventilation, were positive for S aureus colonisation of the lower respiratory tract, as assessed by quantitative PCR (qPCR) analysis of endotracheal aspirate, and had not been diagnosed with new-onset pneumonia. Patients were excluded if they had confirmed or suspected acute ongoing staphylococcal disease; had received antibiotics for S aureus infection for more than 48 h within 72 h of randomisation; had a Clinical Pulmonary Infection Score of 6 or higher; had an acute physiology and chronic health evaluation II score of 25 or higher with a Glasgow coma scale (GCS) score of more than 5, or an acute physiology and chronic health evaluation II score of at least 30 with a GCS score of 5 or less; had a Sequential Organ Failure Assessment score of 9 or higher; or had active pulmonary disease that would impair the ability to diagnose pneumonia. Colonised patients were randomly assigned (1:1:1), by use of an interactive voice or web response system, to receive either a single intravenous infusion of suvratoxumab 2000 mg, suvratoxumab 5000 mg, or placebo. Randomisation was done in blocks of size four, stratified by country and by whether patients had received systemic antibiotics for S aureus infection. Patients, investigators, and study staff involved in the treatment or clinical evaluation of patients were masked to patient assignment. The primary efficacy endpoint was the incidence of S aureus pneumonia at 30 days, as determined by a masked independent endpoint adjudication committee, in all patients who received their assigned treatment (modified intention-to-treat [ITT] population). Primary safety endpoints were the incidence of treatment-emergent adverse events at 30 days, 90 days, and 190 days after treatment, and the incidence of treatment-emergent serious adverse events, adverse events of special interest, and new-onset chronic disease at 190 days after treatment. All primary safety endpoints were assessed in the modified ITT population. This trial is registered with ClinicalTrials.gov (NCT02296320 ) and the EudraCT database (2014-001097-34). Findings: Between Oct 10, 2014, and April 1, 2018, 767 patients were screened, of whom 213 patients with confirmed S aureus colonisation of the lower respiratory tract were randomly assigned to the suvratoxumab 2000 mg group (n=15), the suvratoxumab 5000 mg group (n=96), or the placebo group (n=102). Two patients in the placebo group did not receive treatment after randomisation because their clinical conditions changed and they no longer met the eligibility criteria for dosing. As adjudicated by the data monitoring committee at an interim analysis, the suvratoxumab 2000 mg group was discontinued on the basis of predefined pharmacokinetic criteria. At 30 days after treatment, 17 (18%) of 96 patients in the suvratoxumab 5000 mg group and 26 (26%) of 100 patients in the placebo group had developed S aureus pneumonia (relative risk reduction 31·9% [90% CI −7·5 to 56·8], p=0·17). The incidence of treatment-emergent adverse events at 30 days were similar between the suvratoxumab 5000 mg group (87 [91%]) and the placebo group (90 [90%]). The incidence of treatment-emergent serious adverse events at 30 days were also similar between the suvratoxumab 5000 mg group (36 [38%]) and the placebo group (32 [32%]). No significant difference in the incidence of treatment-emergent adverse events between the two groups at 90 days (89 [93%] in the suvratoxumab 5000 mg group vs 92 [92%] in the placebo group) and at 190 days (93 [94%] vs 93 [93%]) was observed. 40 (40%) patients in the placebo group and 50 (52%) in the suvratoxumab 5000 mg group had a serious adverse event at 190 days. In the suvratoxumab 5000 mg group, one (1%) patient reported at least one treatment-emergent serious adverse event related to treatment, two (2%) patients reported an adverse event of special interest, and two (2%) reported a new-onset chronic disease. Interpretation: In patients in the ICU receiving mechanical ventilation with qPCR-confirmed S aureus colonisation of the lower respiratory tract, the incidence of S aureus pneumonia at 30 days was not significantly lower following treatment with 5000 mg suvratoxumab than with placebo. Despite these negative results, monoclonal antibodies still represent one promising therapeutic option to reduce antibiotic consumption that require further exploration and studies. Funding: AstraZeneca, with support from the Innovative Medicines Initiative Joint Undertaking.